2022
DOI: 10.3390/w14091343
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Traditional Open Levee System for River Flood Mitigation in Japan

Abstract: An open levee system is a traditional flood mitigation system for reducing the expansion of inland flooding and decreasing the peak flow. However, there have been few quantitative studies on its feasibility. Furthermore, the differences in applicability depending on the topography and the construction of continuous levees have not been fully examined. We studied its feasibility based on simulations in the Kuji River area, where the vast Typhoon Hagibis occurred. Morphological models representing the past (the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…Water can be retained when a flood occurs through discontinuous parts of a levee. The flooded areas can be used as farmland or paddy fields, because one purpose of open levee construction is to accumulate organic matter during floods (Teramura and Shimatani 2021), and it is also found that open levees can play a role in flood mitigation (Ohtsuki, Itsukushima, and Sato 2022).The introduction of an SFPA has potential to promote flood mitigation strategies utilizing open levees. In fact, before the introduction of modern technology of Western countries, flooded water in rural areas was not constrained within a river bank but freely inundated, which was the standard approach to mitigate flood damage (Takahasi 2012).…”
Section: Open Levee: Indigenous River Engineering Methods For Flood M...mentioning
confidence: 99%
“…Water can be retained when a flood occurs through discontinuous parts of a levee. The flooded areas can be used as farmland or paddy fields, because one purpose of open levee construction is to accumulate organic matter during floods (Teramura and Shimatani 2021), and it is also found that open levees can play a role in flood mitigation (Ohtsuki, Itsukushima, and Sato 2022).The introduction of an SFPA has potential to promote flood mitigation strategies utilizing open levees. In fact, before the introduction of modern technology of Western countries, flooded water in rural areas was not constrained within a river bank but freely inundated, which was the standard approach to mitigate flood damage (Takahasi 2012).…”
Section: Open Levee: Indigenous River Engineering Methods For Flood M...mentioning
confidence: 99%
“…River levees play a vital role in global flood protection efforts by acting as crucial barriers against increasingly frequent and intense extreme weather events, safeguarding lives, infrastructure, and valuable land from the devastating impacts of flooding [1,2]. Additionally, river levees play a critical role in enhancing climate resilience by adapting to changing hydrological patterns, safeguarding urban and agricultural areas, and promoting economic stability [3,4].…”
Section: Introductionmentioning
confidence: 99%